Training guide on integrated pest management in tobacco. - Bateman, Melanie; Chernoh, Erica; Holmes, Keith A; Grunder, Julien; Grossrieder, Manfred (CABI, 2016)
This Training Guide provides training material to address training needs and offers guidance on how to adapt the core material to local conditions through the national training programmes. This Training Guide focuses on the some of the key principles of integrated pest management (IPM) and appropriate use of crop protection agents (CPAs), such as insecticides, fungicides and herbicides. Through training on the topics in the Training Guide, farmers and field technicians will learn tactics for reducing unnecessary CPA use, they will find out how to select less toxic CPAs which are registered for use on tobacco, and in particular they will learn how to manage CPAs appropriately. This Training Guide is targeted at the core training team in each country. The core teams will be responsible for leading the implementation of their national training programmes. The goal of the Training Guide is to provide them with the necessary tools to design and implement a training programme to support the implementation of IPM and appropriate use of CPAs. This Training Guide presents a core training package with detailed curricula to address all aspects of responsible CPA management.